1998
DOI: 10.1089/vim.1998.11.19
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lymphocytes by HHV-6 Antigen in Normal Children and Adults

Abstract: We investigated the immune reaction of lymphocytes in response to human herpes virus-6 (HHV-6) in normal children and adults. Cell proliferation was assayed by measurement of the incorporation of 5-bromo-2'-deoxyuridine (BrdU) by enzyme-linked immunosorbent assay (ELISA), and changes in expression of interleukin-2 receptors (IL-2Rs) (alpha-, beta3-, and gamma-chain) were assayed by flow cytometry. Incorporation of BrdU and expression of IL-2Rs (alpha-, beta-, and gamma-chain) in CD4+, CD8+, and CD45RO+ lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Early studies established T cell proliferative responses to HHV-6 in most healthy adults (69,81,87). Subsequent studies using peripheral blood mononuclear cells (PBMCs) have demonstrated T cell responses by both CD4 ϩ and CD8 ϩ T cells (24,40,77). However, HHV-6-specific T cell clones and T cell lines (TCLs) have been established only for CD4 ϩ T cells (40,42,69,80,81,87).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies established T cell proliferative responses to HHV-6 in most healthy adults (69,81,87). Subsequent studies using peripheral blood mononuclear cells (PBMCs) have demonstrated T cell responses by both CD4 ϩ and CD8 ϩ T cells (24,40,77). However, HHV-6-specific T cell clones and T cell lines (TCLs) have been established only for CD4 ϩ T cells (40,42,69,80,81,87).…”
mentioning
confidence: 99%
“…Subsequent studies using peripheral blood mononuclear cells (PBMCs) have demonstrated T cell responses by both CD4 ϩ and CD8 ϩ T cells (24,40,77). However, HHV-6-specific T cell clones and T cell lines (TCLs) have been established only for CD4 ϩ T cells (40,42,69,80,81,87). The fine specificity of the T cell response to HHV-6 is largely unexplored.…”
mentioning
confidence: 99%
“…After primary infection, human herpes viruses establish a lifelong latent infection in the host and persist in certain host cells. Latently infected cells may express virus-specific antigens on their cell surface ( 15 , 17 ). However, to protect themselves from immuno-recognition, human herpes viruses have a limited viral gene expression during latency ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The virus can reactivate under conditions of deficient cell-mediated immunity [20]. Although immunity to HHV-6B could evolve over time, there is evidence that lifelong responses to HHV-6B are imprinted very early after the first onset of HHV-6B infection [21]. Neonates are usually protected from HHV-6B infection by maternal-derived antibodies until titers wane over 3–9 months after birth, making older children susceptible to infection [22].…”
Section: Hhv-6b Protective Immunitymentioning
confidence: 99%